2020
DOI: 10.1371/journal.pone.0242215
|View full text |Cite
|
Sign up to set email alerts
|

Active foot placement control ensures stable gait: Effect of constraints on foot placement and ankle moments

Abstract: Step-by-step foot placement control, relative to the center of mass (CoM) kinematic state, is generally considered a dominant mechanism for maintenance of gait stability. By adequate (mediolateral) positioning of the center of pressure with respect to the CoM, the ground reaction force generates a moment that prevents falling. In healthy individuals, foot placement is complemented mainly by ankle moment control ensuring stability. To evaluate possible compensatory relationships between step-by-step foot placem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
96
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(108 citation statements)
references
References 38 publications
9
96
3
Order By: Relevance
“…In previous work, we found that walking with constrained ankle moments, wearing a customized shoe (LesSchuh), decreased foot placement accuracy (van Leeuwen et al, 2020). The LesSchuh is a shoe on which it is almost impossible to use mediolateral ankle moment control, due to a narrow ridge attached to the shoe’s sole.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous work, we found that walking with constrained ankle moments, wearing a customized shoe (LesSchuh), decreased foot placement accuracy (van Leeuwen et al, 2020). The LesSchuh is a shoe on which it is almost impossible to use mediolateral ankle moment control, due to a narrow ridge attached to the shoe’s sole.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work showed that foot placement can be predicted by the full body center of mass kinematic state during the preceding swing phase (Hurt et al, 2010; Mahaki et al, 2019; van Leeuwen et al, 2020; Wang and Srinivasan, 2014). The quality of foot placement control can thus be quantified as the predictability of foot placement based on center of mass kinematic state or proxies thereof.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both passive dynamics and active control are thought to be used by central nervous system to control gait stability [1,2]. Different stabilizing strategies such as ankle [3][4][5], foot placement [1,[5][6][7][8][9][10][11][12][13], hip [9,14,15] and push-off [14,16] strategies are used to control gait stability. To better understand the control of gait stability, external lateral stabilization devices have been used to manipulate medio-lateral stability [6,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Moving the base of support, a stepping response, is the only option to stabilize as is demonstrated with increases in walking speed [ 12 , 13 ]. Moreover, MOS variability reveals information about step-to-step variations in the control of foot placement [ 6 , 14 16 ]. Increased MOS variability may be reflective of increased frequency of adjustments and corrective responses of foot placements in response to the environment or task demands [ 6 , 14 ].…”
Section: Introductionmentioning
confidence: 99%